Early vasopressin infusion improves oxygenation in infants with congenital diaphragmatic hernia - Capolupo, Irma; De Rose, Domenico Umberto; Mazzeo, Francesca; Monaco, Francesca; Giliberti, Paola; Landolfo, Francesca; Di Pede, Alessandra; Toscano, Alessandra; Conforti, Andrea; Bagolan, Pietro; Dotta, Andrea (Frontiers in Pediatrics, 2023)
Objective: Congenital Diaphragmatic Hernia (CDH) is a complex disease including a diaphragmatic defect, lung hypoplasia, and pulmonary hypertension. Despite its increasing use in neonates, the literature on the use of vasopressin in neonates is limited. The aim of this work is to analyze the changes in clinical and hemodynamic variables in a cohort of CDH infants treated with vasopressin. Methods: Among CDH infants managed at the Neonatal Intensive Care Unit (NICU) of our hospital from May 2014 to January 2019, all infants who were treated with vasopressin, because of systemic hypotension and pulmonary hypertension, were enrolled in this retrospective study. The primary outcome was the change in oxygenation index (OI) after the start of the infusion of vasopressin. The secondary outcomes were the changes in cerebral and splanchnic fractional tissue oxygen extraction (FTOEc and FTOEs) at near-infrared spectroscopy, to understand the balance between oxygen supply and tissue oxygen consumption after the start of vasopressin infusion. We also reported as secondary outcomes the changes in ratio of arterial oxygen partial pressure (PaO2) to fraction of inspired oxygen (FiO2), heart rate, mean arterial pressure, serum pH, and serum sodium. Results: We included 27 patients with isolated CDH who received vasopressin administration. OI dramatically dropped when vasopressin infusion started, with a significant reduction according to ANOVA for repeated measures (p= 0.003). A global significant improvement in FTOEc and FTOEs was detected (p=0.009 and p=0.004, respectively) as a significant reduction in heart rate (p= 0.019). A global significant improvement in PaO2/FiO2 ratio was observed (p< 0.001) and also at all time points: at 6 hours since infusion (p= 0.015), 12 hours (p= 0.009), and 24 hours (p=0.006), respectively. A significant reduction in sodium levels was observed as expected side effect (p= 0.012). No significant changes were observed in the remaining outcomes. Conclusion: Our data suggest that starting early vasopressin infusion in CDH infants with pulmonary hypertension could improve oxygenation index and near-infrared spectroscopy after 12 and 24 hours of infusion. These pilot data represent a background for planning future larger randomized trials to evaluate the efficacy and safety of vasopressin for the CDH population.